Terminal invasion [videorecording (Blu-Ray)] - Campbell, Bruce, 1958-; Masterson, Chase, 1963-; Johnson, C. David (Christopher David), 1955-; Lafleur, Sarah (Kino Lorber, 2023)
Inside an isolated airport, seven anxious passengers learn that their charter flight has been grounded by a blizzard. The unhappy passengers are soon stunned into silence by the arrival of Jack Edwards, a convicted murderer escorted by two guards. But these soon prove to be the least of the passengers' problems, as they realize that some members of the group are not who, or what, they seem.